2014
DOI: 10.1088/1674-1056/23/4/047202
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-induced hole injection-enhanced photoluminescence in a N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-benzidine-based emitter

Abstract: Non-monotonic, asymmetrical electric field dependence of photoluminescence (PL) intensity is observed in a monolayer sample of tris-(8-hydroxyquinoline) aluminum (AlQ) doped N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-benzidine (TPD). A possible model is proposed: the charge separation from the dissociated photoexcited excitons causes energy band bending in the organic films and improves the hole injection from the electrode, which brings about the extra fluorescence. This mechanism is further verified by a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Conductivity is an important factor that can greatly impact the performance of devices, such as organic photovoltaic (OPV), organic light emitting diodes (OLED). [1][2][3][4][5] However, the conductivity of organic small molecular materials is still poor compared with traditional inorganic materials because of their low charge mobility and low carrier density. [6,7] In 2001, Zhou et al found that the conductivity of TDATA can be greatly increased by F4-TCNQ doping.…”
Section: Introductionmentioning
confidence: 99%
“…Conductivity is an important factor that can greatly impact the performance of devices, such as organic photovoltaic (OPV), organic light emitting diodes (OLED). [1][2][3][4][5] However, the conductivity of organic small molecular materials is still poor compared with traditional inorganic materials because of their low charge mobility and low carrier density. [6,7] In 2001, Zhou et al found that the conductivity of TDATA can be greatly increased by F4-TCNQ doping.…”
Section: Introductionmentioning
confidence: 99%